Air pollution and autism in Denmark. Issue 4 (December 2018) - Ritz, Beate; Liew, Zeyan; Yan, Qi; Cuia, Xin; Virk, Jasveer; Ketzel, Matthias; Raaschou-Nielsen, Ole
Abstract : Background: Previous autism spectrum disorder (ASD) and air pollution studies focused on pregnancy exposures, but another vulnerable period is immediate postnatally. Here, we examined early life exposures to air pollution from the pre- to the postnatal period and ASD/ASD subtypes in the Danish population. Methods: With Danish registers, we conducted a nationwide case–control study of 15, 387 children with ASD born 1989–2013 and 68, 139 population controls matched by birth year and sex identified from the birth registry. We generated air dispersion geographic information system (AirGIS) model estimates for nitrogen dioxide (NO2 ), sulfur dioxide (SO2 ), particulate matter 2.5 (PM2.5 ), and particulate matter 10 (PM10 ) at mothers' home from 9 months before to 9 months after pregnancy and calculated odds ratios (ORs) and 95% confidence intervals (CIs), adjusting for parental age, neighborhood socioeconomic indicators, and maternal smoking using conditional logistic regression. Results: In models that included all exposure periods, we estimated adjusted ORs for ASD per interquartile range (IQR) increase for 9 months after pregnancy with NO2 of 1.08 (95% CI = 1.01, 1.15) and with PM2.5 of 1.06 (95% CI = 1.01, 1.11); associations were smaller for PM10 (1.04; 95% CI = 1.00, 1.09) and strongest for SO2 (1.21; 95% CI = 1.13, 1.29). Also, associations for pollutants were stronger in more recent years (2000–2013) and in larger cities compared with provincial towns/rural counties. For particles and NO2, associations were only specific to autism and Asperger diagnoses. Conclusions: Our data suggest that air pollutant exposure in early infancy but not during pregnancy increases the risk of being diagnosed with autism and Asperger among children born in Denmark. Abstract : Supplemental Digital Content is available in the text.